Pengaruh Kompos dan PGPR (Plant Growth Promoting Rhizobacteria) Pada Lahan Kering Terhadap Produksi Sawi (Brassica rapa L.) - Farida Puput Kurniasih; Raden Soedrajat (Fakultas Pertanian Universitas Jember, 2019)
The increasing of demand for agricultural product and the narrowing of fields where fields are currently being prioritized for cultivating food crops forcing them to take and use dry land. Problem happened by conducting agricultural activities on dry land such as limited water availability, low microorganism population and low nutrient avaibility. Water avaibility on dry land can be optimized by providing compost and PGPR. The productivity of Sawi nauli varieties according to the minister of agriculture decision (2009) that 37-39 tons/ha with a population per hectare are 93.000 plants. This purpose of this study is to determine the effect of compost and PGPR on dry land about pakchoy productivity. This study also used factorial completely randomized design and replicated 3 times. The design of two treatments are: The first: compost which consists of 4 levels with a dose of 5 kilograms of soil, 4900 grams of soil with 100 grams of compost, 4800 grams of soil with 200 grams of compost, 4700 grams of soil with 300 grams of compost. For the second factor is PGPR which consists of 4 levels with a dose of 0 milligrams/plant, 100 milligrams/plant, 200 milligram/plant and 300 milligram/plant. The data obtained were analyzed by using analysis of variance (ANOVA). Then, the results obtained from the ANOVA test were followed by the Standart Error Mean (SEM). Based on the results of the study it is known that there are influences from each single factor and combination of treatments. Compost treatment showed significantly different results on variable number of leaves, number of leaf chlorophyll and dry weight of plants. Whereas there is a very significant effect on plant height and plant fresh weight. On a single factor PGPR showed no significant results on variable plant height, number of leaf chlorophyll, but showed a significant effect on variable number of leaves, plant fresh weight and plant dry weight. The combination of compost and PGPR treatment showed no significant results on variable plant height, number of leaves, number of leaf chlorophyll, and plant dry weight. The treatment combination treatment showed a significant effect on the fresh weight variable of the plant